Pillpop Final Year Group Project Report - Sarah Nsereko; Daphine Kamusiime; Nkata Joshua Luyombya; Mukisa Hassan Bahati; Kasagga Gordon Kimera; Allan Smith Niringiye (Uganda Christian University, 2024)
A web application aimed at reminding users to take their medications which is a major problem in Uganda also called medication non-adherence called Pillpop was developed to solve this problem with additional features to further solve this problem, The application was developed due to a recent study on the health sector, which displayed that medication non-adherence is one of the problems troubling the health sector. Moreover, the problem was reflected in my lifestyle when it came to taking medications. The development of the application was done based on using email as a format of reminding users and all the other features within rotated based on the user’s data. Using different technologies e.g Nextjs and Django to develop the application, which relies on the data storage or backend a lot, and displays through the frontend hence the need for an interface that is easy to navigate for the users. During the application development, a lot of hostility was found especially when it came to collecting data and the effectiveness of reminding a user which is hard to achieve 100% because it all draws back to user integrity and I found that it not possible to solve all the problems within the one application but instead one problem at a time is better. The significance of the findings is that investment in technology can help or improve the efficiency of health since the digital generation/age is now the common or the norm meaning with the help of technology, the health of the users can improve, and it also a call to find ways of utilizing the available technology to improve one’s life quality .